The Legal Implications of the Indonesian Standard Industrial Classification for the Position of Notaries as Public Officials - Arabella Kezia Putri Maulina; Amelia Sri Kusuma Dewi; Dewi Iryani (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2027)
This study aims to analyze the legal position of a Notary as a public official following the classification of notarial activities under the Indonesian Standard Industrial Classification Number 69104, as well as to examine the legal certainty of such regulation within the Indonesian legal system. This research employs a normative legal research method with statutory, conceptual, and comparative approaches, using primary, secondary, and tertiary legal materials. The research gap in this study lies not only in the absence of scholarly analysis linking the Indonesian Standard Industrial Classification as a risk-based business licensing instrument with the position of Notaries as public officials, but also in the lack of examination specifically addressing the normative implications of categorizing public office activities within a business-law regime. Previous studies have generally focused either on the position of Notaries from the perspective of the Notary Law, or on Indonesian Standard Industrial Classification within the context of business licensing administration in general, without situating both within a unified framework of normative conflict and legal system harmonization. The findings indicate that the classification of notarial activities under Indonesian Standard Industrial Classification Number 69104 has the potential to create normative disharmony, as it places the activities of a Notary within a business-oriented economic framework, whereas a Notary’s authority derives from state attribution to perform public service functions. This condition reflects a conceptual shift from a public office to an administrative entity governed by business licensing mechanisms, which is not fully aligned with the legal construction of the Notary position under the Notary Law. The novelty of this research lies in three main aspects. First, it explicitly constructs the normative conflict between the risk-based business licensing regime (Indonesian Standard Industrial Classification 69104) and the legal regime governing Notaries as public officials. Second, it employs a synthesis of the theory of authority and the theory of legal certainty as analytical instruments to assess the validity of such regulation within the Indonesian administrative legal system. Third, it offers a normative harmonization perspective that positions Indonesian Standard Industrial Classification not merely as an administrative instrument, but as a variable capable of shifting the juridical character of the Notary office within Indonesia’s constitutional and administrative legal framework .